PREDICTIVE MARKET TRENDS IN PRINTING AND PHOTOGRAPHY - Mahajan, Vibhor; Joshi, Chaitanya; Goel, Pooja; Karthik K; Mundada, Dipali Kapil; Misra, Dolly (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The printing and photography sectors are changing very fast due to digitalization, automation and using data to make decisions. The analysis of market trends which can be predicted as a key to the analysis of the demand fluctuations, the technological use, and the changing preferences of consumers in such visual-oriented sectors. This paper will examine the predictive market trends in printing and photography by using a combination of economic indicators, technological drivers and behavioral data into a single analysis tool. To capture both the macroeconomic and the micro-level market dynamics, the study uses heterogeneous sources of data, which are industry reports, sales records, online platforms, and social media trend signals. Premature preprocessing and feature engineering are used to derive temporal, economic and behavioral cues to express pricing frameworks, production expenses, personalization demand, sustainability inclinations, and transformations in visual culture. Several different predictive modeling approaches will be considered, including classical time-series like ARIMA, SARIMA, Prophet, or machine learning models like regression, random forest, and gradient boosting or deep learning models like LSTM, GRU, or transformer-based predictors. Comparative analysis reveals that hybrid, as well as deep learning models, are strong in terms of capturing non-linear trends and long term dependencies of creative markets.